The effectiveness of the JAKIM halal logo on Malaysia consumers' confidence in manufacturing food - Mohamed, Zainalabidin; Rezai, Golnaz; Shamsudin, Mad Nasir; Eddie, Chiew Fook (2010)
The introduction of halal logo by the Malaysian Department of Islamic Development (JAKIM) has triggered a greater awareness among the Muslim communities about the importance of consuming products or engaging in services that follow Islamic guidelines and principles. In March 2006, the Prime Minister of Malaysia Datuk Seri Abdullah Ahmad Badawi announced that all state governments had been directed to use the standard halal logo issued by JAKIM, thus making the logo the national halal logo of Malaysia. Unfortunately there is a lack of enforcement in monitoring the usage of certified halal logo causing the public to question the validity of some of the products that are claimed to be halal. The objectives of this study are to gather information on consumers’ perception towards the JAKIM halal logo and to assess the level of confidence of the halalness of food products which carry this logo. A sample of 600 Muslim respondents, were interviewed via structured questionnaires to derive their confidence level and purchasing behavior towards food products which come with halal logo. Descriptive statistics were used to describe the socioeconomic/ demographic background and the perception of the respondents. Meanwhile the logit model was used to determine the extent to which selected socio-economic/demographic characteristics and perception influenced the respondents’ confidence on halal logo. The results of this study suggest that consumers are very concerned about halal food and halal logo on food products. Many consumers react more positively to JAKIM halal logo, although there is still evidence to support that consumers are more careful in evaluating the halalness of all kinds of food products by referring to the list of ingredients. Nevertheless, most consumers are able to differentiate between JAKIM halal logo from the other logos, regardless of the brands on the food products.